Intregrasi Asuhan Kebidanan Modern dan Tradisional pada Adat Dayak - Dian Purnama Putri; Sefentina Agustin; Aliya Aliya; Aviliyani Aviliyani (Pusat riset dan Inovasi Nasional, 2025)
Integration between traditional and modern midwifery care practices is a very important strategic step in efforts to improve the quality of maternal health services, especially in indigenous communities such as the Dayak tribe. This article aims to explore the opportunities and benefits that can be obtained from combining the two approaches, including how this integration can improve maternal and child health outcomes. The method used in this study is a qualitative method with a literature study approach. The conclusion of this study is that there is a relationship between traditional and modern midwifery care practices. Traditional practices that contain cultural, spiritual, and local experience values ​​have been shown to provide a sense of security for pregnant women. On the other hand, the modern midwifery approach provides the clinical basis and medical interventions needed in high-risk conditions.